Propriedades eletrônicas e estruturais do Cu/ZrO2 aplicadas à reação do etanol - Sato, André Gustavo (2012)
Copper is a typical catalyst for dehydrogenation of ethanol to acetaldehyde. However, copper supported on ZrO2 was found to be extremely active and selective to convert ethanol directly to ethyl acetate. Several reports in the literature have been made attempting to explain the catalytic properties of the solid Cu/ZrO2. Nevertheless, the nature of active sites, the role of copper, ZrO2 and their interface require further study with the use of more accurate techniques. Since the precise identification of the active sites for the occurrence of this reaction is the first step to propose mechanisms that help to understand it. In this work, we conducted a study using copper supported on three different polymorphs of ZrO2: monoclinic (m-ZrO2), tetragonal (t-ZrO2) and amorphous (am-ZrO2). Thus, the interaction of copper phase with ZrO2 would be limited to changes in textural, structural and electronic properties intrinsic to each polymorph, and not to the chemical composition in the case of we chose other support oxide. With an innovative and challenging proposal, this thesis developed by itself conducting in advanced characterizations of the structure and electronic state of the Cu/ZrO2 activated in H2. The analytical approach adopted for the characterization of the Cu/ZrO2 was performed by monitoring its in situ activation by the temperature programmed reduction in H2 with technique using synchrotron radiation like X-ray Absorption spectroscopy. Although reactions in heterogeneous catalysis proceed on the surface of an active catalyst, the properties of the surface can be influenced or determined by the bulk of the catalyst. X-ray photoelectron spectroscopy and diffuse reflectance infrared Fourier transform spectroscopy of adsorbed CO were used for Cu/ZrO2 active surface characterization. Catalytic tests show that the direct and efficient formation of ethyl acetate from ethanol depends on the chemical interface between Cu-ZrO2. However, it was found that higher performance of these catalysts to ethyl acetate does not occur at any interface. The property of Cu-ZrO2 interface varies according to the ZrO2 polymorphism, with the best performance in the ethyl acetate formation observed in the catalyst Cu/m-ZrO2. The premature loss in ethyl acetate selectivity observed at temperatures above 250 °C in Cu/m-ZrO2 revealed that the origin of its interface property can be associated with the oxygen mobility and lability from the bulk of the catalyst. Through the redox mechanism promoted by oxygen vacancies in am-ZrO2 and in m-ZrO2, an electron transfer between support and Cu surface would be established as to form highly active species to ethyl acetate.